TREATMENT OF ROOT PERFORATION WITH INDICATION FOR EXTRACTION AND IMPLANT-SUPPORTED REHABILITATION - Giacomo Gobbo Trojan; Pamela Rufina Stefanello Wideck; Adria Myllene Pinto de Barros; Nicolly Menezes de Oliveira; Katiane Vieira Menezes Leite; Leonel Souza de Oliveira; Saymon Calixto Rodrigues; Thiago Andre Cruz da Costa (International Journal of Health Management Review, 2026)
Root perforations occurring during endodontic instrumentation are primarily associated with iatrogenic errors, technical limitations, and a lack of awareness regarding anatomical variations. Proper treatment planning, combined with the use of supplementary diagnostic tests, is essential for enhancing treatment safety and predictability. In the event of complications or treatment failure, an individualized assessment of the tooth's prognosis becomes imperative. Although tooth preservation is the primary goal of endodontic treatment, extensive perforations—or those with a poor prognosis for repair and sealing—may necessitate tooth extraction. In such cases, rehabilitation with dental implants offers an effective alternative for restoring function and aesthetics, based on the patient's clinical, biological, and anatomical conditions.